PENINGKATAN HASIL BELAJAR AKIDAH AKHLAK MELALUI PENGGUNAAN MEDIA AUDIO VISUAL PADA PESERTA DIDIK IV MIN 7 BANDAR LAMPUNG - Andriani; Gustin Rifaturrofiqoh; Ridho Agung Juwantara (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2022)
The purpose of this research is to find out the improvement of Aqidah Akhlak learning outcomes of students through Audio Visual media in Class IV students of MIN 7 Bandar Lampung. Preliminary data shows that many students still have difficulty following lessons, many student complaints related to the contextualization of material to real life, and the most concrete is indicated by low learning outcomes. This research is a type of Classroom Action Research using activity instruments and learning outcomes. Data collection by performing actions in Cycle I and Cycle 2 using Observation, Test and Documentation tools. Furthermore, analysis, preparation and publication are carried out. The cycle used is planning, implementation, observation, and reflection. The findings of Learning Activities show that in the pre-cycle only 26.5%, the first cycle increased by 42.5%, the second cycle increased to 78.5%, so that the increase from pre-cycle to second cycle was 52%. The finding of completeness of student learning outcomes also showed an increase in the first cycle of 57.1% with the category